Incidence of osteomuscular injuries related to the work of woodworkers in the Municipality of São João del-Rei and region (Research, Society and Development, 2021)
Repetitive Strain Injuries or Work-Related Musculoskeletal Disorders (RSI/WMSD) are related to precarious and exhausting working conditions. RSI/WMSD affect carpentry workers, presenting the following symptoms: localized pain, radiating pain, paresthesia, feeling of heaviness, fatigue, discomfort and loss of strength. In the municipality of São João Del-Rei and region, there is a large number of self-employed workers in carpentry. The aim of the study was to evaluate the incidence of RSI/WMSD in a sample of woodworkers from São João Del-Rei/MG and region. The study is of the original type, quantitative and has a cross-sectional design. The sample number was 29 woodworkers, who were submitted to the Nordic Musculoskeletal Symptoms Questionnaire (NMSQ). The inclusion criteria were to be carpentry workers in São João Del-Rei and region, who agreed to participate in the research and signed the Informed Consent Term. In the last 7 days, 24.14% (n=7) of the participants reported pain, and 48.83% (n=13) of these reported pain in the lower back. In the last 12 months, 27.59% (n=8) of the participants reported pain, and 37.93% (n=11) had pain in the wrist or right hand, 75.86% (n=22) in the region lumbar and 27.59% (n=8) in the ankles or feet. As for pain intensity on a scale of 1 to 10, mean pain intensity was 6.33 in the right elbow, 5.5 in the left elbow, 5 in the thoracic region, 6.1 in the lumbar region, 6 in the ankles or feet. The main complaints were pain in the lower back, cervical spine, ankles and feet. It is concluded that carpentry leads to joint and muscle overload, and ergonomic instructions can help maintain health at work.